Oil and Gas Field Development Use Floating Production Storage and Offloading (FPSO) in Improving the Economic Aspect of Company in the Gross Split Scheme - Purnomo Rusdiono, Asep Handaya Saputra (International Journal of Advanced Science and Technology, 2020)
The development of marginal oil and gas fields in the offshore area in the Gross SplitProduction Sharing Contract (PSC) scheme has technical and economic challenges. Thisresearch focuses on economic analysis of the development of marginal offshore oil andgas fields. The field development method uses scenario development with FloatingProduction Storage and Offloading (FPSO) with two production time scenarios, ScenarioI with a production time of 7 years and Scenario II with a production time of 10 years.Economic analysis uses capital budgeting indicators, such as NPV, IRR, and PaybackPeriod. An economic evaluation was carried out to find the best method for developingmarginal oil and gas fields by applying the Gross Split PSC scheme. It is expected fromthe development scenario, it can improve the company's economy. The sensitivity analysisis then performed to determine the sensitivity of the following parameter changes: theamount of production, oil and gas prices, capital costs (CAPEX), production operatingcosts (OPEX), and incentive tax affect the value of NPV, IRR and the Government take.The results show that the best scenario is Scenario I with production time 7 years. Theeconomic analysis show that Scenario I is attributed to NPV of USD 29.1 million, IRR of30.2% with Payback Period in year 2026.